Schema therapy conceptualization of personality functioning and traits in ICD-11 and DSM-5. Issue 1 (January 2019) - Bach, Bo; Bernstein, David P.
Abstract : Purpose of review: Schema therapy conceptualizes personality disorders in terms of modes and underlying schemas. This article reviews the literature on schema therapy conceptualization of personality disorder functioning and traits, and proposes how these findings apply to novel personality disorder classification in ICD-11 and the DSM-5 Alternative Model of Personality Disorders (AMPD). Recent findings: Maladaptive schemas and modes are generally associated with personality dysfunction and traits in conceptually coherent ways. The healthy adult mode, a transdiagnostic core concept in schema therapy, corresponds to the ICD-11 and DSM-5-AMPD features of core personality functioning. Modes and underlying schemas substantially overlap with specific ICD-11 and DSM-5-AMPD traits, which denote individual themes and styles of personality dysfunction. Summary: The dimensional personality disorder framework in ICD-11 and DSM-5-AMPD is largely compatible with the schema therapy model. The ICD-11 and DSM-5-AMPD provide a scientifically derived and theory-free framework for all practitioners, which may be connected to clinical theory of schema therapy in a coherent manner. Level of personality functioning can be conceptualized as healthy adult functioning (e.g. sense of identity, self-worth, emotion regulation, intimacy, and fulfillment), which inform intensity of treatment. Trait qualifiers can be conceptualized by associated modes (e.g., compliant surrender) and underlying schemas (e.g. abandonment), which inform focus and style of treatment.